Peran Customer Value dalam Memediasi Pengaruh Monetary Sacrifice dan Service Benefit Terhadap Repurchase Intention - Qurananda, Angga Cahya; Giantari, I Gusti Ayu Ketut (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan; Volume 14 Nomor 1 Tahun 2020, 2020)
Repurchase intentions occur when service users or customers are satisfied and get what they need. This study aims to determine the effect of monetary sacrifice and service benefits on repurchase intention mediated by customer value. This research was conducted on customers of PT. Garuda Indonesia Persero Tbk. The number of samples taken was 112 respondents, with nonprobability sampling method. Data collection was obtained from distributing questionnaires. Data analysis using path analysis and multiple test. The results of this study indicate that monetary sacrifice has a positive effect on customer value. Service benefit has a positive effect on customer value. Monetary sacrifice has a positive effect on repurchase intention. Service benefit has a positive effect on repurchase intention. Customer value has a positive effect on repurchase intention. Monetary sacrifice positively influences repurchase intention mediated by customer value. Service benefit has a positive effect on repurchase intention mediated by customer value. The implication of this research is expected to be a reference for the management of PT. Garuda Indonesia Persero Tbk. in providing benefits in the form of good service and giving a special impression to customers.